Pengembangan Aplikasi Media Ajar Untuk Meningkatkan Kemampuan Motorik Kasar di sekolah Dasar - Aliudin Aliudin; Akhmad Sobarna; Sumbara Hambali (Universitas Hamzanwadi, 2026)
Physical Education, Sports, and Health instruction in elementary schools still faces challenges in the form of monotonous conventional methods, minimal use of technology, and low student engagement, resulting in students’ gross motor skills not developing optimally. This study aims to develop a digital-based instructional media application to improve the gross motor skills of elementary school students and to test its feasibility and effectiveness. The study used the Research and Development (R&D) method with the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of 32 students. The instruments used included a TGMD-2-based gross motor skills test, a student response questionnaire, and an expert validation form. The results of the expert validation showed an average score of 4.27 (highly feasible) for the content and 4.33 (highly feasible) for the media. The large-scale pilot test showed an average increase in scores from the pretest (66.10) to the posttest (82.30) of 24.51%, with a t-test yielding a calculated t-value of 7.85 > the critical t-value of 2.04 (p < 0.05) and an effect size of 1.52 (very large effect). Analysis by motor aspect showed the highest improvement in locomotor movements (24.6%). Positive responses from students reached 86% and from teachers 90%. The conclusion of this study is that the developed instructional media application is deemed highly suitable and effective in improving the gross motor skills of elementary school students.